01 DOSE ESCALATION WITH ORIGINATOR INFLIXIMAB IS MORE COMMON THAN STANDARD DOSING IN PEDIATRIC IBD – THE DEVELOP EXPERIENCE. (7th February 2019) - Griffiths, Anne; Escher, Johanna; Izanec, James; Busse, Christopher; Wang, Yanli; Dubinsky, Marla
Abstract: Background: DEVELOP is a multicenter, prospective, observational registry of the long-term safety and clinical status of 6070 pediatric patients with inflammatory bowel disease (IBD; Crohn's disease [CD]: 4122, ulcerative colitis [UC]: 1643, and IBD-unclassified[IBD-U]: 305; median age at enrollment 13.0 years) treated with originator infliximab (REM) and/or other medical therapies for IBD as part of routine clinical care. DEVELOP has sites in the United States, Canada and the EU and enrolled patients from 2007 to 2017. The labelled maintenance dose and interval of REM for treatment of pediatric CD or UC is 5mg/kg IV every 8 weeks. Our aim was to assess how frequently providers needed to escalate this dose. Methods: Enrollment was targeted such that half of the enrolled patients had been exposed to REM at baseline. The treating physicians then continue to prescribe IBD treatments based on their usual clinical practice and standards of care. Patients are categorized into cohorts according to their prevalent or incident IBD medication exposure, including patients receiving therapy prior to enrollment and patients receiving therapy during registry follow-up. The last data cut available (June 30 2018) assessed 33, 586.4 patient years (PY) of follow up. Results: Approximately half of the registry population (47.5%) was exposed to REM prior to enrollment, with similar breakdown by IBD diagnosis (CD: 47.5%; UC: 46.4%; and IBD-U: 54.1%). An additional 20.1% (23.0% of CD patients, 14.5% of UC and 12.5% of IBD-U) were exposed on or after their baseline visit, giving a total of 67.7% of all patients in DEVELOP (Table 1). Among all patients, the median average maintenance dose of REM thus far during the registry period is 6.5 mg/kg (CD: 6.1 mg/kg, UC: 7.5 mg/kg and IBD-U: 8.0 mg/kg). The median maintenance dosing frequency was 8 weeks for CD patients, 7 weeks for UC patients and 6 weeks for IBD-U patients (Table 2). In the most recent 12-month follow up period, the median total number of REM infusions was 17.0, with a median duration of REM exposure of 32.3 months and a mean duration of 38.9 months. During the entire registry follow up period, 27.3% of patients who had been receiving REM discontinued the drug. The median interval between first dose and discontinuation was 20.9 months and the most common reasons for discontinuation were loss of efficacy (47.0% of discontinuations), adverse events (17.2%) and administration reactions (13.3%). Conclusion: In the international DEVELOP pediatric IBD registry, standard dosing of REM is the exception rather than the rule. The median maintenance doses used in CD, UC and IBD-U are all higher than the labelled dose of 5 mg/kg. In UC and IBD-U, the median maintenance interval is also shorter than the labelled interval of q8 weeks. Further analysis will examine clinical measures before and after dose escalation.